From Green Programs to Green Souls: Cultivating Environmental Character Through School-Based Ecological Interventions - Muhamad Abdul Gofur; Pepi Andraini; Ilham Jaya (Wildan: Jurnal Pendidikan dan Pengajaran - STAI Bani Saleh, 2025)
This study examines Green School program implementation and its implications for instilling environmental care character in elementary students. Using a descriptive qualitative case study approach at SDIT Arkan Cendekia, Bekasi, data were collected through observation, interviews, and documentation over four months (April-July 2025). Findings reveal systematic program implementation through waste management, greening, energy efficiency, and behavioral habituation, supported by the entire school community. The program creates clean, healthy learning environments while significantly contributing to character formation evidenced by increased responsibility, discipline, and environmental awareness. However, challenges persist in maintaining consistency during holidays and sustaining student motivation. This study contributes a micro-level analysis of character transformation processes—the transition from 'green programs' to 'green souls'—offering a replicable framework for environmental education in Islamic elementary schools.